PEMIMPIN IDEAL MENURUT PANDANGAN PEMILIH PEMULA DI KOTA SEMARANG DALAM PEMILIHAN PRESIDEN DAN WAKIL PRESIDEN TAHUN 2014 - Amarona Akdasenda; Yuwanto .; Rina Martini (Journal of Politic and Government Studies, 2014)
In 2014, Indonesia will be held of President and Vice President elections. Candidates for President and Vice President are they which derived from political party ,Even it from mixed political party ( coalitions ) that have met the requirements of has got 20% of DPR, DPD, and DPRD seats. The presidential elections in 2014 will be carried out in accordance with Law (Undang-undang) No 42 of 2008 about the election of a President and Vice President.Purpose of this research which to know ideal leader according to young voters in Semarang based on President and Vise President election 2014. This research uses the type of exploratory data analysis of quantitative.Based on these data, it will be examined in research is how ideal leader according to young voters in the next president and vise president election. Of the research results, it can be concluded that ideal leader according to young voters is leaders who are not legally flawed, leaders who have a sense of concern for his members and leaders who have a clear vision and mission.Political party can make this research as a barometer to find or establish of nominee leaders who will advance to the next presidential election. Political party in determining of nominee leaders who will advance as participants presidential election, should pay attention to the criteria that have been described in this research. Political parties should be able to maximize the regeneration function in finding prospective leaders really needed and envisioned by each community.Keywords: The Early Voters, , Ideal Leader, Presidential Election 2014